PENGGUNAAN LAYANAN GO-PAY PADA MAHASISWA UPN VETERAN JAKARTA - Mochammad Rizki Pratama (2021)
Along with the development of an increasingly modern era, all activities cannot be separated from the existence of technology. Various new innovations are needed in this digital era so that all human activities become more efficient, safe, and comfortable, especially in the implementation of world economic activities. One method of financial services that is gaining popularity in the current digital era is the financial technology industry (fintech). The technology-based payment system is one of the sectors in the Fintech industry that is very developed and popular among the people of Indonesia. In Indonesia, financial technology transactions continue to increase from year to year. This increase is in line with the increasing use of mobile payment services in Indonesia. Go-Pay is an example of financial technology in the payment system sector. Go-Pay is an alternative for making transactions on the Go-Jek application.